PEMBUATAN WEBSITE NAGARI LUBUK KARAK SEBAGAI IMPLEMENTASI DARI GERAKAN INDONESIA MELAYANI - Reinaldo Shandev Pratama; Dina Putri; Azrimaidaliza Azrimaidaliza (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2019)
Website is a feature that is commonly used for various purposes, ranging from the actualization of individuals, business institutions in dealing with the community of users of services or products, to become a digital face for official agencies such as government. One of the Nagari who needs the benefits of this website is Lubuk Karak, District IX Koto, Dhamas Raya Regency. This is because complaints and aspirations are still very dependent on physical meetings between community representatives and the head of the Jorong, with the guardian of the village. With the existence of the village website, it is hoped that it can become a digital medium to accommodate complaints and aspirations of the community and increase community interaction and communication with the staff of the religion. Through the KKN Mental Revolution activity, students are expected to become agents of change by socializing and inviting people to make changes in line with the values of mental revolution. One of the work programs carried out by thematic KKN students of Andalas University spiritual revolution is the creation of a Nagari website, this program as a form of the Indonesian service movement. This Website Creation begins with training activities and introduction to the Nagari website created by Andalas University, namely the village Information System and the submission of the website that has been made to Nagari Lubuk Karak with the address